Determinants of entrepreneurial intention among school students in Malaysia: An empirical study - Vijeyan Samydevan; Mohd Rushidi Mohd Amin; Shishi Kumar Piaralal (Taylor & Francis, 2020)
This study investigated the determinants of entrepreneurial intention, namely entrepreneurial self-efficacy, risk propensity, innovativeness, tolerance to ambiguity, individualism, collectivism and power distance and also the mediating effect of entrepreneurial self-efficacy among school students in Malaysia. A questionnaire survey was used to collect the data, and purposive sampling was employed. A total of 351 students from the state of Johor, Malaysia, were involved and this study used Smart-PLS 3.0 to analyze the data. The results showed that collectivism and power distance had an insignificant relationship with entrepreneurial intention. Meanwhile, entrepreneurial self-efficacy was found to have a partial mediating effect on the relationship between risk propensity and entrepreneurial intention. (Abstract by authors)